Removal of iron (ii) using various activated sludge - Siti Norazizah, Jamil (2010)
The activated sludge is used as biological material to absorb the iron (II) in the contaminate wastewater. The objective of this research is to determine the best activated sludge at various sizes for removal of iron (II) in aqueous solution. Exposed to the iron greater than 0.3 mg/L may cause water staining that adversely affect plumbing fixtures, dishware, and produce a yellow to reddish appearance in water. The activated sludge were collected from different sources of industry include Palm Oil Mill Effluent, Food Industry and Polymer Industry. The activated sludge was dried up 12 hour at 105˚C. Solutions of 500mg/L of iron (II) sulphate are prepared as stock solution. The aqueous solution was mixed with the absorbent starting at 100 minutes until 200 minutes contact time. The solution and the activated sludge was separate using the centrifuged within 15 minutes at 3800 RPM. UV-Vis spectrometer at a 510nm wavelength was used to analyze the iron (II) concentration. The result show 77.5% of iron (II) removal efficiency was attained in the Polymer Industry dried activated sludge with 45µm size and 200 minutes of contact time. Meanwhile, Food Industry and Palm Oil Mill Effluent are 66% and 72% respectively.